‘Man up and get on with it’: a qualitative exploration of UK ex-serving personnel’s experiences of seeking help for self-harm and suicidal behaviours - Charlotte Williamson; Walter Busuttil; Amos Simms; Laura Palmer; Sharon A. M. Stevelink; Marie-Louise Sharp (European Journal of Psychotraumatology)
Background: A substantial proportion of UK military personnel experiencing mental health problems do not seek professional support. Although the promotion of help-seeking is a key suicide prevention strategy, little is known about help-seeking for self-harm and suicidal behaviours among the UK Armed Forces.Objective: This study aimed to explore UK ex-serving personnel’s experiences of seeking help for self-harm, suicidal ideation, and suicide attempts.Method: Participants were recruited via an existing longitudinal cohort study exploring the health and well-being of the UK Armed Forces. A subgroup of ex-serving personnel reporting lifetime self-harm and/or suicidal behaviours was invited to participate in semi-structured interviews and 15 individuals participated, representing help-seekers/non-help-seekers and formal/informal support. Interviews were analysed using reflexive thematic analysis.Results: Five distinct but related and interacting themes were developed: (1) military mindset; (2) stigma; (3) fear of consequences; (4) access to and awareness of support; and (5) facilitators to help-seeking.Conclusions: Help-seeking decisions and experiences were influenced by several barriers and facilitators. Providing an environment where military populations feel willing and able to access support for self-harm and suicidal behaviours could lessen the impact on their health and well-being and ultimately save lives.